A comparative study of different rapid visual survey methods used for seismic assessment of existing buildings. (February 2021) - Bhalkikar, Aniket; Pradeep Kumar, R.
Abstract: Determination of seismic safety of existing buildings is a time consuming and challenging process. Instead, rapid survey methods were developed which identify deficient structures from a large building stock in a city or town. This paper presents a comparison and critical review of existing rapid visual survey methods used for seismic assessment of existing reinforced concrete buildings. The study focuses on rapid visual survey methods developed for the safety assessment of reinforced concrete buildings in the Indian subcontinent and a widely used method in the United States. Comparison is carried out in various ways. Initially, a direct comparison is made based on vulnerable parameters and damage grades proposed by each method. Later, a scoring system is developed to highlight the differences and rank the selected methods. This system considers the general description, physical parameters, and damage description. Finally, as a case study, a rapid visual survey was conducted on 100 reinforced concrete buildings in each of the three cities (i.e., Pithoragarh, Gangtok, and Agartala) in India. These cities have different seismic, geological, and topographical conditions. The results show that all five methods give different outputs for the same sample surveyed buildings in each city. It was observed that there are many uncommon vulnerability parameters amongst each selected method. The results show a considerable variation in the weights assigned to each vulnerable parameter in all five methods.